Endothelin but Not Angiotensin II May Mediate Hypertension-Induced Coronary Vascular Calcification in Chronic Kidney Disease - Simon W. Rabkin (International Journal of Nephrology)
To understand the relationship between putative neurohormonal factors operative in hypertension and coronary artery calcification (CAC), the relevant cellular actions of angiotensin (Ang II) and endothelin-1 (ET-1) are reviewed. There is compelling evidence to implicate ET-1 in CAC. ET-1 increases phosphate transport with a 42 to 73% increase in Vmax. Increased cellular phosphate may induce CAC through increased Ca x phosphate product, transformation of vascular smooth muscle cells into a bone-producing phenotype or cell apoptosis that releases procalcific substances. ET-1 is increased in several models of vascular calcification. ET-1 inhibits inhibitors of calcification, matrix Gla and osteoprotegerin, while enhancing pro-calcific factors such as BMP-2 and osteopontin. In contrast, Ang II inhibits phosphate transport decreasing Vmax by 38% and increases matrix Gla. Ang II also stimulates bone resorption. Vascular calcification is reduced by ET-1 A receptor antagonists and to a greater extent than angiotensin receptor blockade although both agents reduce blood pressure.